منهج مجلس العلماء الإندونيسي في إصدار الفتوى : دراسة تحليلية نقدية - إبراهيم، أسامة أحمد فلق (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This thesis aims to reveal the methodology employed by the Indonesian Council of Ulama (MUI) in issuing fatwa. This thesis also elaborates three natures of the methodology in the MUI fatwa formulation process and forms of the decided fatwa. In this study, the author conducts a critical review on various books concerning MUI. This thesis also presents the history of the formation of the National MUI, and provincial MUIs, which were established earlier than the National MUI. The author then describes procedural relationship between fatwa release processes in the National MUI and those in the provincial MUIs. In this thesis, the author also conducts an analysis method to critically review the MUI's fatwa development methodology. It can be summarized that there are some values from MUI; the main objective of MUI's establishment is to produce fatwa, provide advice, and opinion about Muslim communities and government. The methodology applied by MUI to release fatwa is based on the Qur'an and Hadith, the opinion of 'ulama fiqh, and 'ijtihad approach. For the 'ijtihad approach, MUI should clarify more on the references used to release fatwa.